2013
DOI: 10.1016/j.nicl.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Multi-delay multi-parametric arterial spin-labeled perfusion MRI in acute ischemic stroke — Comparison with dynamic susceptibility contrast enhanced perfusion imaging

Abstract: The purpose of the present study was to present a multi-delay multi-parametric pseudo-continuous arterial spin labeling (pCASL) protocol with background suppressed 3D GRASE (gradient and spin echo) readout for perfusion imaging in acute ischemic stroke. PCASL data at 4 post-labeling delay times (PLD = 1.5, 2, 2.5, 3 s) were acquired within 4.5 min in 24 patients (mean age 79.7 ± 11.4 years; 11 men) with acute middle cerebral artery (MCA) stroke who also underwent dynamic susceptibility contrast (DSC) enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
292
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(302 citation statements)
references
References 18 publications
7
292
2
1
Order By: Relevance
“…Sequences that account for this variability in arterial arrival time (AAT) can be used to improve the reliability of ASL; thereby supporting its use to image more complex conditions where cerebral perfusion may be undermined by a particular pathology. 21 Recent work supports this by showing that: (1) it is possible to account for heterogeneity in AAT by incorporating multiple PLDs; 22,23 (2) acquisition of multiple PLDs improves the accuracy of CBF quantification by facilitating the removal of the macrovascular component of the ASL signal. 24 At present, no study has assessed the within-and betweensession reproducibility of multi-PLD pCASL.…”
Section: Introductionmentioning
confidence: 88%
“…Sequences that account for this variability in arterial arrival time (AAT) can be used to improve the reliability of ASL; thereby supporting its use to image more complex conditions where cerebral perfusion may be undermined by a particular pathology. 21 Recent work supports this by showing that: (1) it is possible to account for heterogeneity in AAT by incorporating multiple PLDs; 22,23 (2) acquisition of multiple PLDs improves the accuracy of CBF quantification by facilitating the removal of the macrovascular component of the ASL signal. 24 At present, no study has assessed the within-and betweensession reproducibility of multi-PLD pCASL.…”
Section: Introductionmentioning
confidence: 88%
“…According to the previous works, DSC MTT is different from transit time in ASL imaging. ASL transit time is defined as the duration time for the labeled blood between labeling region and brain tissue, whereas DSC MTT represents the mean time for contrast agent to traverse from the arterial to the venous end (19,29). It noted that transit time in ASL is conceptually similar with DSC Tmax.…”
Section: Fig 2 the Graphs Show The Correlations Between Asl Cbf Andmentioning
confidence: 99%
“…In stroke assessment in which the hypoperfused area is identified, good correlations have been shown between ASL and DSC MRI parameters, including Tmax and MTT (8,19). It has also shown that DSC Tmax could assess the effect transit time on ASL perfusion (19).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ASL has also been reported to provide information regarding the presence of collateral cortical flow using both CASL and PASL. 25,[27][28][29][30] The studies of the teams of Chalela, using CASL, 27 Viallon, using flow-sensitive alternating inversion recovery (FAIR) as an example of a PASL technique, 30 and Wang, using pCASL, 31 reported the cases of patients presenting with hyperperfusion in the ischemic territory. They explained hyperperfusion corresponding to bright intravascular signal with delayed arterial transit and luxury perfusion previously demonstrated by PET study.…”
Section: Discussionmentioning
confidence: 99%